In vitro assessment of antimicrobial, antioxidant, and cytotoxic properties of Saccharin-Tetrazolyl and-Thiadiazolyl derivatives: the simple dependence of the pH value on antimicrobial activity - Frija, Luís M. T. (2020)
The antimicrobial, antioxidant, and cytotoxic activities of a series of saccharin-tetrazolyl and -thiadiazolyl analogs were examined. The assessment of the antimicrobial properties of the referred-to molecules was completed through an evaluation of minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values against Gram-positive and Gram-negative bacteria and yeasts. Scrutiny of the MIC and MBC values of the compounds at pH 4.0, 7.0, and 9.0 against four Gram-positive strains revealed high values for both the MIC and MBC at pH 4.0 (ranging from 0.98 to 125 µg/mL) and moderate values at pH 7.0 and 9.0, exposing strong antimicrobial activities in an acidic medium. An antioxidant activity analysis of the molecules was performed by using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method, which showed high activity for the TSMT (N-(1-methyl-2H-tetrazol-5-yl)-N-(1,1-dioxo-1,2-benzisothiazol-3-yl) amine, 7) derivative (90.29% compared to a butylated hydroxytoluene positive control of 61.96%). Besides, the general toxicity of the saccharin analogs was evaluated in an Artemia salina model, which displayed insignificant toxicity values. In turn, upon an assessment of cell viability, all of the compounds were found to be nontoxic in range concentrations of 0-100 µg/mL in H7PX glioma cells. The tested molecules have inspiring antimicrobial and antioxidant properties that represent potential core structures in the design of new drugs for the treatment of infectious diseases.